Lakor Goat, The Indonesia Original Livestock Cluster From Maluku - Siwa, Isak P. (Kalwedo Sains (KASA), 2020)
Agriculture Development reorientati on farm system and agribusiness based on local natural recourcesso that development policies are sustable to rill condition and lacation specific. The district of Southwest Maluku has specific livestock that is categorized as local hybrid Vigoranimal husbandry i.e Lakor island goat, which is called â€œKambing lakorâ€. Field research shows the goat of Lakor have a comparative advantage in term of reproduction characteristic and fenotypr characteristic advantage. Based on this comparative advantage, Lakor goats has been stated by government as Indonesian Livestock Cluster from Maluku.